Delivery of multipotent adult progenitor cells via a functionalized plasma polymerized surface accelerates healing of murine diabetic wounds - Mills, S. J.; Kirby, G. T.; Hofma, B. R.; Smith, L. E.; Statham, P.; Vaes, B.; Ting, A. E.; Short, R.; Cowin, A. J. (Frontiers in Bioengineering and Biotechnology, 2023)
Stem cell therapies have been investigated as potential treatment modalities for chronic wounds however there has been limited success to date. Multipotent Adult Progenitor Cells (MAPCs©) have been identified as having potential as an allogenic stem cell product due to their high population doubling number and their characteristic dampening of T-cell proliferation. This helps to prevent autoimmunity and graft/cell rejection. We have developed a dressing, consisting of medical grade silicone coated with a heptylamine plasma polymer, which supports the growth and transfer of MAPCs to skin. To determine if the dressing can deliver functional stem cells into diabetic wounds, they were loaded with MAPCs and then placed over excisional wounds in both normal and diabetic mice. Accelerated healing was observed in both the normal and diabetic wounds with wound areas being significantly smaller at day 3 and 7 when compared to controls. Wound analysis showed that treatment with the MAPC dressings dampened the inflammatory response with reduced numbers of neutrophils and macrophages observed. Additionally, an increase in pro-angiogenic VEGF and CD31 positive endothelial cells was observed indicating improved new blood vessel formation. The MAPC dressings had no effect on fibrosis with collagen I and III being equally affected in both control and treated wounds. Overall, the functionalized MAPC dressings improve healing responses particularly in diabetic mice with impaired healing responses and therefore, show potential for development as an advanced therapeutic approach for the treatment of chronic diabetic wounds.